Evaluation of the response given to the vitamin D treatment in patients with osteomalacia - Omer Genc; Fatih Kılıçlı; Selin Genç (SERNEV, 2022)
Introduction: The current study aimed to examine the relationship between 25 hydroxyvitamin D [25(OH)D] levels and demographic, clinical and laboratory parameters and response to treatment in patients living in a Central Anatolian city of Turkey and diagnosed with osteomalacia.Methods: A total of 533 patients who live in the continental climate, older than 18 years old, and have 25(OH)D levels lower than 30 ng/ml were enrolled prospectively. Patients' age, body mass index (BMI), type of clothing, season in which they were diagnosed, type of treatment and duration were recorded. At the time of diagnosis, the patients were evaluated with clinical and laboratory parameters at 1st, 2nd, and 4th months.Results: Mean serum 25(OH)D level was 7.59±4.41 ng/mL at the time of diagnosis. 25(OH)D level was 24.42±14.77 ng/ml after treatment, with severe deficiency ( lt;10 ng/mL) in 74% of patients, deficiency ( lt;20 ng/mL) in 24.2%, insufficiency in 1.3% (20-29.99 ng/mL). 74.4% of the women had a closed clothing style. Vitamin D levels during diagnosis and at the end of treatment did not differ according to the BMI and the diagnosis period (p gt; 0.05). However, as BMI increased, the response given to the treatment decreased.Conclusions: The current study showed that vitamin D deficiency is common in study population. The current findings demonstrate that treatment and follow-up should be continued until achieving normal serum 25(OH)D levels, taking into account geographic and ethnical structures to bring vitamin D levels to adequate levels.Keywords: 25-hydroxytamin D; Osteomalacia; vitamin D deficiency